‘Mapping the terrain of servicescape research in the hospitality industry: an analysis of hotels and restaurants’ - Anusha Pai; Dasharathraj K. Shetty; Sandeep S. Shenoy; Shreepathy R; Nikita Panwar (Cogent Social Sciences, 2025)
The study gives a detailed analysis of the prior work in the hotel and restaurant sector. The research synthesizes the academic literature on Servicescape in the hotel and restaurant industry by carrying out a bibliometric analysis identifying common themes, areas of agreement and identifies gaps in the research that can guide future studies. 147 papers from the database maintained by Scopus, produced between 1995 and 2022, were analyzed for the study. The research breaks out the most important publications, prolific writers, leading journals, and countries, as well as the publishing trends. The review findings uncovered satisfaction, servicescape, social servicescape, hospitality, atmospherics, COVID-19, customer service, service quality, customer satisfaction, students, and place attachment as the major clusters. The study findings guide all stakeholders and point to more research in this domain.